SCHOOL SANITATION AND HYGIENE EDUCATION IN INDIA - Dr. Humera Nuzhat (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2025)
School is important for cognitive, creative and social development of children. So is the School Sanitation and Hygiene Education, necessary for the safe, secure and healthy environment for children to learn better and face the challenges of future life. Maintaining personal hygiene and sanitation is important for several reasons such as personal, social, psychological, health, etc. Proper hygiene and sanitation prevent the spread of diseases and infections. If every individual on the planet maintains good hygiene for himself and the things around him, diseases will eradicate to a great level. This understanding is very much a part of the policy of Government of India (GoI). From policy to programme, School Sanitation and Hygiene Education (SSHE) has now become a reality of school centric development action being realized by most of the schools. Government of India has launched this programme integrating with broader sanitation program to ensure that all the schools especially rural schools in the nation have basic sanitation and drinking water facilities and good hygiene practices are taught to the children. The School Sanitation and Hygiene Education programme is participatory in nature and an important component of the national reforms programme for rural water and sanitation sector. Many of the challenges, which the programme in India faces, are similar to those of other countries. Approach, strategy, and mode of implementation may differ but the vision associated it remains the same. Sharing these may offer insights and serve as a starting point for cross-learning and further improvement of the programme.